Counselling in a Nutshell - Dryden, Windy (London : SAGE, 2006)
Focusing on the commonalities within the main theoretical approaches - psychodynamic, person-centred and cognitive-behavioural - Windy Dryden describes a framework which underpins all counselling, irrespective of the approach being used.
Includes bibliographical references (p. 124-126) and index.
Keywords: Counseling; Counselor and client; Psychology